1958
DOI: 10.1172/jci103593
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine-Binding by Serum Protein in Pregnancy and in the Newborn

Abstract: Thyroid structure and function in man undergo a number of changes during pregnancy. The thyroid gland may become enlarged and hyperplastic (1, 2), thyroidal uptake of radioiodine is increased (3, 4), "conversion" of blood iodide to organic form is more rapid (4), and the serum proteinbound iodine (PBI) is elevated (5, 6). Although these alterations are like those seen in hyperthyroidism, they appear to be associated, in early pregnancy at least, with an unequivocally euthyroid state. Whereas the PBI rises as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0
6

Year Published

1960
1960
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 32 publications
4
37
0
6
Order By: Relevance
“…in maternal blood are in accordance with the reports of other investigators who have found these changes to be characteristic of pregnancy [16,20,22]. The increase in TBG cap.…”
Section: Discussionsupporting
confidence: 92%
“…in maternal blood are in accordance with the reports of other investigators who have found these changes to be characteristic of pregnancy [16,20,22]. The increase in TBG cap.…”
Section: Discussionsupporting
confidence: 92%
“…Some investigators have found higher mean Plil and bulanol-extracted iodine values in maternal blood at delivery than in cord blood [3, fi, 10, 18]. while others have found no dilference [2,9,17,22,23,25]. We have shown that maternal blood thyroxine levels are slightly, but significantly, higher than those in cord samples.…”
Section: Discussionmentioning
confidence: 39%
“…), 21,25]; others have found values comparable to those of maternal serum [3]. Because FT., is calculated as the product of total thyroxine and FT.,F in serum, the discrepancies in FT 4 reported from different laboratories can partly be explained by clillerent methods used to estimate thyroxine in serum.…”
Section: Discussionmentioning
confidence: 91%
“…This increase in TBG level is due to the increase in estrogen concentration, resulting in a rise of TBG production and release by the liver, site of synthesis of the protein [11]. Furthermore, the circulating levels of both albumin and prealbumin remain stable, with only a discrete tendency to decrease near term, consequently to the hemodilution [13]. The respective affinities of the three binding proteins for TH are not significantly modified.…”
Section: Thyroid Hormones Transport Proteinsmentioning
confidence: 99%